Akulturasi Budaya Lampung Dan Cina Pada Nuwo Tantan Gumanti - Marzius Insani; Syaiful M; Valensy Rachmedita; Rinaldo Adi Pratama (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRACT The research aims to find and explore the history and acculturation of Lampung and Chinese in the house of Nuwo Tantan Gumanti. The research method is descriptive and data analysis using descriptive analysis. The results of this research showed that there was cultural acculturation between Lampung and China in the house of Nuwo Tantan Gumanti, including glass with Chinese ornaments such as phoenixes, snakes, butterflies and the colorful glass on the top of the window and above the room door. There are also Chinese scripts that are still clearly visible on the connecting wood and the walls of the house. The roof of Nuwo Tantan Gumanti is different from other houses in Lampung community, because the shape of a pyramid, and the pillars are rectangular and have pegs that are connected to them. From the research results It can be concluded that there is a cultural acculturation between Lampung and China in the Nuwo Tantan Gumanti architecture on several sides of the building. Keywords: Acculturation, Architecture, Culture, China, Lampung, Nuwo.